Relationship among five‐factor personality traits and psychological distress with acoustic analysis - Saeed Saeedi; Payman Dabirmoghaddam; Mehdi Soleimani; Mahshid Aghajanzadeh (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objectives The relationship between personality traits and psychological distress with acoustic characteristics was investigated in the present study, regarding the existence of dysphonia, abnormal overall voice quality (AOVQ), and dysphonia type. Methods Fifty‐five participants with dysphonia and 64 participants without dysphonia completed NEO Five‐Factor Inventory and Depression, Anxiety, and Stress Scale‐21. Jitter, shimmer, noise‐to‐harmonic ratio (NHR), cepstral peak prominence (CPP), and cepstral peak prominence‐smoothed (CPPS) were calculated in sustained vowel /a/ by Praat. Three expert speech and language pathologists divided participants with dysphonia into mild, moderate, and severe, based on the AOVQ. Pearson and Spearman correlation tests were performed by IBM SPSS Statistics. Results The findings were indicative of large correlations between agreeableness with CPP, conscientiousness with shimmer, depression with jitter and shimmer, and anxiety with shimmer in patients with functional dysphonia (p < 0.05). The results showed small to medium significant correlations between agreeableness with jitter and NHR, conscientiousness with CPP in participants without dysphonia, and depression with jitter in the participants with dysphonia (p < 0.05). Lastly, no significant correlation was observed between personality traits and psychological distress with acoustic characteristics in mild, moderate, and severe AOVQ groups (p > 0.05). Conclusion In participants with functional dysphonia, personality traits and psychological distress can provide some information about acoustic characteristics and vice versa. Level of Evidence 3.